ANALISA DAYA SAING (COMPETITIVE ADVANTAGE) INDUSTRI PERHOTELAN BINTANG 3 DI BANGKA BELITUNG, DITINJAU DARI TAMPILAN BERBASIS SUMBER DAYA INTERNAL (INTERNAL RESOURCE BASED VIEW), STUDI KASUS GRAND VELLA HOTEL - Dicky; Ruben Manullang, Rizal; Panjaitan, Fery (Jurnal Progresif Manajemen Bisnis, 2018)
Hotel is one of the companies engaged in the services, which focus on customer service. But in a very tight competition, many competitors are in the same field and compete with each other for the market, so that is not only needed excellent services, but a lot of factors to keep customers survive and attract new customers to come, therefore, every business player in the hotel industry is required to have a good strategy in order to continue to compete. One such strategy is to conduct an internal resource-based view. Grand Vella Hotel is one of the business players in the hotel industry, especially three starred-hotels, in the Bangka Belitung Island region, especially in the Pangkalpinang area. To improve competitiveness, Grand Vella Hotel implements an internal resource-based view strategy. The analysis consists of three important elements, namely: financial resource analysis, human resource analysis, and organizational assets and core competency analysis.